تقويم محتوى كتاب الرياضيات للصف السابع الأساسي في اليمن في ضوء مها ا رت القرن الحادي والعشرين - احمد, ريهان علي قاسم; المعمري, سليمان عبده أحمد (Journal of Amran University, 2022)
The study aimed to evaluate the mathematics book for the 7th-grade in Yemen in the light of twenty-first century skills, and to identify the extent to which the 7th-grade students have acquired them. The Study adopted the analytical descriptive approach, and the list of analyzing the content of the mathematics book in the light of the twenty-first century skills was used to analyze the content of a book in addition to using a test to measure the skills of the twenty-first century for the 7th-grade students. The sample of the study consisted of the content of the mathematics book scheduled for students of the seventh grade in Yemen where the analysis of the mathematics textbook for students in the first and second semesters of the academic year (2019-2020) edition (1436 ah / 2017 ad) was analyzed in addition to measuring the extent of students' possession of seventh grade in Taiz governorate, Al-shamayaten districts of these skills during the second semester of the year 2019-2020 ad. the study found that the availability of twenty-first century skills in the content of the mathematics textbook for the 7th-grade in Yemen was low by (15.71), which is a very weak percentage. The results found that the level of students ’possession of the twenty-first century skills came at a rate of (37%), which is very weak compared to the acceptable rate (65%). The results also showed that there were statistically significant differences at the level of (0.05) due to the gender variable in favor of (females). The study concluded with a set ofrecommendations, the most important of which was the necessity to include mathematics books for the basic stage with the twenty-first century skills and teach them to students of that stage.